Do social responsibility disclosures show improvements on stock price? - Jizi, Mohammad (2016)
The 2007 financial crisis was the largest shock to the financial markets not only to the United States but the world as a whole since 1930. Lack of information and confusion in financial markets causes sharp declines in banks capitalization. The link between stock price behavior and the content of social disclosure is lacking in the literature and there is no clear understanding whether they are valued or disregarded by financial markets. CSR is the voluntary interaction between the firm and its stakeholders through addressing their social and environmental concerns with business activities. This paper contributes to the literature by drawing conclusions on whether CSR disclosure, which communicates firm involvement and level of commitment to society, shows improvement on banks' stock prices. Banks' social behavior is equally important to investors and customers risk assessment on one hand, and to regulators' reputation and the public confidence in the banking system on the other hand. Poorly controlled and operated banks can impose extensive negative effects not only on investors but also on their societies; therefore, effective management manages risk not only through financial performance but also through reflecting their good citizenship. The research examines a sample of national commercial banks, as the banking sector was experiencing increasing pressure that scratched stakeholders and investors trust during the latest financial crisis. In addition to examining a unique sample of banks during 2009-2010, the study contributes by employing content analysis technique to measure the content; i.e. the existence and comprehensiveness; of CSR disclosure in banks' annual reports. We find that the informative content of CSR disclosure is appreciated by stock participants and is of value. The reported results signal investors' interest in and consideration to CSR disclosure when valuing assets. Moreover, our results suggest that management involvement and communication of their CSR activities through better disclosure content is a potential tool to enhance shareholders value. The documented results are likely to encourage banking institutions in the developing countries to invest and report on their social activities. Banking institutions may enhance their shareholders welfare by investing in effectual social engagements and considering the content of CSR disclosure rather than classifying social involvement as nonrewarding activity.